2017
DOI: 10.1177/0093854817721936
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Postincarceration Social Support for Emerging Adults

Abstract: More than 2.5 million emerging adults (ages 18-25) are incarcerated annually and most do poorly after release. Social support after an individual’s release from incarceration is a critical protective factor against recidivism for emerging adults. However, little is known about the stability of support for emerging adults post incarceration. This study uses hierarchical linear modeling (HLM) to examine whether social support declines over time after incarceration and how change in support may vary by incarcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…This is a noteworthy contribution because only one longitudinal study, to our knowledge, has examined the dynamic relationship between support providers after confinement. Pettus-Davis and colleagues (2017) found that increases in family (mostly expressive) support corresponded with decreases in nonfamily support and vice versa. In examining more precise forms of support received through relationships, we found that parents and partners substitute for each other when providing instrumental support (partially supporting Hypothesis 4a).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…This is a noteworthy contribution because only one longitudinal study, to our knowledge, has examined the dynamic relationship between support providers after confinement. Pettus-Davis and colleagues (2017) found that increases in family (mostly expressive) support corresponded with decreases in nonfamily support and vice versa. In examining more precise forms of support received through relationships, we found that parents and partners substitute for each other when providing instrumental support (partially supporting Hypothesis 4a).…”
Section: Discussionmentioning
confidence: 91%
“…Empirical evidence on the interrelationship of support providers after confinement is almost nonexistent, with only one study in Table 1 examining this area. Pettus-Davis and colleagues (2017) found a substitution effect between family and nonfamily providers of support to young adults across multiple waves postconfinement. Their measure of support was blended—comprised primarily of expressive support elements (e.g., talk about trouble, important decisions; care about your feelings), but also some instrumental (e.g., depend on for help).…”
Section: Social Support and Confinement: Expectations And Prior Researchmentioning
confidence: 93%
See 3 more Smart Citations